Mengembangkan Kemampuan Menghadapi Perubahan Dalam Pembelajaran Kelas Rangkap - Azzahra Rindra Tiara; Christin Ananta Putri; Habsah Afifatul Amri; Krisna Farhan Fadillah; Rahmawati; Rosa Ananta Febrianti (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Multi-grade Learning (PKR) is a learning model that is often applied in the 3T (underdeveloped, frontier and outermost) areas as a solution to the limited number of educators. However, implementing this model presents complex challenges that require high adaptive skills from teachers. This article discusses the importance of developing change coping skills for teachers in the context of MGT, including changes in curriculum, education policy, developments in information and communication technology (ICT), and the diverse learning needs of students. PKR teachers are required to be flexible in their learning strategies, classroom management and effective use of simple technology. In addition, teachers also need to develop pedagogical, managerial, evaluative and collaborative competencies to create inclusive and meaningful learning. With strong adaptive skills, PKR teachers are not only able to survive the fluctuating learning dynamics, but also have a significant positive impact on the quality of student education across levels. This article confirms that improving teacher capacity through training and policy support is the main foundation for optimizing learning in multi-grade classrooms.